1993
DOI: 10.1126/science.8384374
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure contributions to function in bioinorganic chemistry

Abstract: Many metalloenzymes exhibit distinctive spectral features that are now becoming well understood. These reflect active site electronic structures that can make significant contributions to catalysis. Copper proteins provide well-characterized examples in which the unusual electronic structures of their active sites contribute to rapid, long-range electron transfer reactivity, oxygen binding and activation, and the multielectron reduction of dioxygen to water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
230
0
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 406 publications
(244 citation statements)
references
References 63 publications
8
230
0
4
Order By: Relevance
“…1 This prominent role has led to a considerable research effort to study the structure and dynamics of these systems with the aim of understanding their function. [2][3][4][5][6][7][8][9] Spectroscopic methods have played an important role in this work. A variety of spectroscopic techniques have been applied to study these proteins, predominantly by Solomon and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…1 This prominent role has led to a considerable research effort to study the structure and dynamics of these systems with the aim of understanding their function. [2][3][4][5][6][7][8][9] Spectroscopic methods have played an important role in this work. A variety of spectroscopic techniques have been applied to study these proteins, predominantly by Solomon and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…Because of favorable combinations of covalency and oxidation/reduction potentials, the activation of molecular oxygen by its coordination to one or two supported ͑i.e., ligated͒ Cu͑I͒ ions is common to a number of biological and inorganic catalytic processes. [26][27][28][29][30][31][32][33][34][35][36][37][38][39] In the case of monocopper species LCuO 2 , where L is a general ligand or ligands, one possible oxidation state that may be assigned to the complex is LCu͑II͒O 2 ͑−͒; thus, the copper atom has been oxidized by one electron and the O 2 fragment is formally a superoxide radical anion. Similarly, in the case of dicopper species ͑LCu͒ 2 O 2 , one possible oxidation state of the complex is formally ͓LCu͑II͔͒ 2 ͓͑O 2 ͒͑2−͔͒; in this instance, each copper atom has been oxidized by one electron and the O 2 fragment is formally a peroxide dianion.…”
Section: Application To Supported Cuo 2 and Cu 2 O 2 Systemsmentioning
confidence: 99%
“…In this homogeneous chemistry, the bis(µ-oxo)dicopper core is capable of isomerizing to the (µ-η 2 :η 2 -peroxo)dicopper core, i.e., [Cu 2 (µ-η 2 :η 2 -O 2 )] 2+ (Structure B) [51,52]. The latter peroxo-dicopper core is also present in the enzyme hemocyanin, found in arthropods and mollusks, where it performs the reversible binding of O 2 [53,54]. Therefore, we suggested that the bis(µ-oxo)dicopper core in Cu-ZSM-5 fulfills the key role of the continuous O 2 release and in this way guarantees the sustained high activity of Cu-ZSM-5 [49].…”
Section: Introductionmentioning
confidence: 99%